2017
DOI: 10.1038/nnano.2016.304
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and pH-universal ruthenium-based catalyst for the hydrogen evolution reaction

Abstract: The hydrogen evolution reaction (HER) is a crucial step in electrochemical water splitting and demands an efficient, durable and cheap catalyst if it is to succeed in real applications. For an energy-efficient HER, a catalyst must be able to trigger proton reduction with minimal overpotential and have fast kinetics. The most efficient catalysts in acidic media are platinum-based, as the strength of the Pt-H bond is associated with the fastest reaction rate for the HER. The use of platinum, however, raises issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
812
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,430 publications
(839 citation statements)
references
References 31 publications
25
812
1
1
Order By: Relevance
“…Recently, Baek and co‐workers have prepared the Ru nanoparticles (NPs) decorated on nitrogenated holey 2D carbon structure (C 2 N) and hybrid comes up with exceptional HER activity by achieving the current density of 10 mA cm −2 at the over potential of 17 mV which is even better than the commercial Pt/C 18. The theoretical studies suggested that when Ru is placed in the holes of C 2 N, the Ru–H 2 O binding energy increases significantly, which results faster water adsorption and accelerates Volmer step.…”
Section: Challenges Associated With Her In Alkaline Mediummentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Baek and co‐workers have prepared the Ru nanoparticles (NPs) decorated on nitrogenated holey 2D carbon structure (C 2 N) and hybrid comes up with exceptional HER activity by achieving the current density of 10 mA cm −2 at the over potential of 17 mV which is even better than the commercial Pt/C 18. The theoretical studies suggested that when Ru is placed in the holes of C 2 N, the Ru–H 2 O binding energy increases significantly, which results faster water adsorption and accelerates Volmer step.…”
Section: Challenges Associated With Her In Alkaline Mediummentioning
confidence: 99%
“…However, the differences in H‐binding energy between alkaline and acidic mediums could not be explained and are still not clear. Furthermore, it has also been found that there are few catalyst that perform better in alkaline medium than the acidic one, although majority of catalysts show better activities in acidic than in the alkaline medium,18, 55, 56, 57 suggesting that there are both qualitative and quantitative differences of the reaction mechanisms between these two mediums. Therefore, a thorough understanding of the reaction mechanisms in alkaline medium is significant to ascertain reactive sites, get insight into the reaction mechanism and tailor new materials for HER.…”
Section: Factors Controlling the Reaction Rate On Catalyst Surface Anmentioning
confidence: 99%
See 2 more Smart Citations
“…The HER mechanism in acidic electrolytes is generally recognized as a combination of three elementary steps: (1) the Volmer step, described as hydronium (H 3 O + ) discharge and formation of an adsorbed intermediate H ad • on the active site (•) (H 3 O + + • + e − → H ad • + H 2 O); (2) either a following Heyrovsky step (H 3 O + + H ad • + e − → • + H 2 + H 2 O) or Tafel step (2H ad • → 2• + H 2 ) 4. In alkaline media, the HER mechanism is similar to that in acidic conditions except that H ad • is formed from dissociation of water (H 2 O + • + e − → H ad • + OH − ), a step with kinetic rate depending on the binding energies of H 2 O and OH ad on the catalyst surface 8, 9, 33. Thus, the kinetic of HER in alkaline electrolytes depends on both the rate of H ad combination and the rate of H 2 O dissociation 9.…”
Section: Introductionmentioning
confidence: 99%